Effect of sugar concentration (°Brix) and storage temperature on the time to visible growth of individual ascospores of six heat-resistant moulds isolated from fruit products. (February 2020) - Lane Paixão dos Santos, Juliana; Samapundo, Simbarashe; Van Impe, Jan; Sant'Ana, Anderson S.; Devlieghere, Frank
Abstract: Heat-resistant moulds (HRMs) pose great challenges to processors of fruit-based products due to their thermal resistance and ability to grow across a broad range of conditions. Therefore, the quantification of the effect of inhibitory factors (conditions) on the growth of HRMs is very important to be used to prevent spoilage during shelf-life. This study assessed the minimum temperature and maximum sugar content (°Brix) for the growth of six HRMs ( Byssochlamys spp. and Neosartorya spp.) previously isolated from fruit products. In addition, the time to form a visible colony (tv, days) was determined to assess biological variability of individual ascospores within same population. Heat activated ascospores (10 min at 80 °C) were spread plated (±100 spores) on acidified Potato Dextrose Agar (aPDA, pH 3.5) plates from which the °Brix was adjusted with fructose-glucose (1:1) to levels between 44 and 59 °Brix followed by incubation at 30 °C. To assess the effect of temperature, inoculated plates of aPDA were incubated at 4, 7, 8, 10, 12 and 14 °C. Three replicates (= 3 aPDA plates) were prepared per condition evaluated. The number of visible colonies were counted daily for up to two months. Probability distribution functions were then fitted in @Risk to the cumulative tv 's. With regards to cold tolerance, B. nivea was the most cold sensitive as it had the least ability to germinate and form visible colonies at low temperatures (no growth when T ≤ 10 °C). On the other hand, N. hiratsukae was the most cold tolerant, being able to form visible colonies at temperatures ≥ 7 °C. Likewise, B. nivea was the most sensitive to increased °Brix values, whilst N. udagawae was able to grow out at the highest °Brix evaluated (59°/aw = 0.86). The tolerance of potential spoilage HRMs to high sugar levels and their ability to grow under chilled conditions represent a challenge for the microbial stability of high-sugar fruit products. Differences in individual tv 's were mostly observed under conditions at the growth/no growth regions. For instance, individual tv 's of B. nivea ascospores ranged from 24 to 46 days at 12 °C and those of N. udagawae ranged from 20 to 45 days at 59°Brix. The tv 's data from each HRM and condition evaluated were then fitted to different statistical distributions (Exponential, Normal, Lognormal, Weibull, Logistic or Pareto) to allow the use of the obtained data in further Quantitative Microbial Spoilage Risk Assessment work for pasteurized fruit products. Highlights: Effect of °Brix and temperature on the time to visible growth (tv ) of six HRMs was assessed. N. hiratsukae was able to form visible colonies under chilled conditions (≥7 °C). N. udagawae was able to form visible colonies up to 59°Brix (aw = 0.86). The tv 's of individual ascospores were fitted to statistical distributions. Wide ranges of tv 's were mainly observed at growth/no growth regions.